PENINGKATKAN KETERAMPILAN MENGENDALIKAN VARIABEL DAN MENDEFINISIKAN VARIABEL SECARA OPERASIONAL MELALUI PEMBELAJARAN LEARNING CYCLE 3E - Dhita Mita Anggra Ovika; Noor Fadiawati; Chansyanah Diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
The aimed this study was to describe the increase of students’ skill in controlling variables and defining variables operationally on Learning Cycle three-phase (LC-3E). The model was applied pretest-posttest control group design. The participants included two clsses at the second year sains of SMA N 1 Way Jepara, Lampung Timur. The increase of students’ skill in controlling variables and defining variables operationally measured on the difference of a significant normalized gain (n-Gain). The results show that mean value of n-Gain controlling variables skill in control and experimental classes were 0.15 and 0.47, and the mean value of n-Gain defining variables operationally skill in control and experimental classes were 0.23 and 0 , 50. Based on hypothesis testing using t-test and n-Gain, it was concluded that the LC 3E learning model can increasing students’ skill in controlling variables and defining variable operationally.Kata kunci: Learning Cycle 3E, keterampilan mengendalikan variabel, dan mendefinisikan variabel secara operasional